2016
DOI: 10.7287/peerj.preprints.1817v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus impairs growth in human neurospheres and brain organoids

Abstract: Since the emergence of Zika virus (ZIKV), reports of microcephaly have increased dramatically in Brazil; however, causality between the widespread epidemic and malformations in fetal brains has not been confirmed. Here, we examine the effects of ZIKV infection in human neural stem cells growing as neurospheres and cerebral organoids. Using immunocytochemistry and electron microscopy, we show that ZIKV targets human brain cells, reducing their viability and growth as neurospheres and cerebral organoids. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 1 publication
2
85
0
1
Order By: Relevance
“…The detection of ZIKV in fetal brains of humans (73)(74)(75)(76)(77) and mice (13,(78)(79)(80) has led to the hypothesis that virus replication in the CNS causes adverse perinatal outcomes. Although ZIKV is detectable in the fetal brain (20,81), we have shown that ZIKV is undetectable in the neonatal brain (13).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of ZIKV in fetal brains of humans (73)(74)(75)(76)(77) and mice (13,(78)(79)(80) has led to the hypothesis that virus replication in the CNS causes adverse perinatal outcomes. Although ZIKV is detectable in the fetal brain (20,81), we have shown that ZIKV is undetectable in the neonatal brain (13).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of Guillain-Barré syndrome is estimated to be 1/5,000 cases Lessler et al, 2016). Congenital malformations and adverse outcomes associated with ZIKV acquisition during pregnancy are likely due to placental infection and viral transmission to the fetus, with the virus displaying a tropism for neuronal cells (Garcez et al, 2016;Miner et al, 2016;Nowakowski et al, 2016;Quicke et al, 2016;Tang et al, 2016). However, ZIKV infection is generally asymptomatic or, in about 20% of the cases, associated with mild and non-specific symptoms (Lessler et al, 2016;Petersen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most notable are microcephaly and other congenital defects in infants born to mothers infected with ZIKV during pregnancy (Mlakar et al, 2016;Petersen et al, 2016;Rasmussen et al, 2016;Wikan and Smith, 2016). Although the exact mech-anism of neuropathogenesis remains uncertain, clinical abnormalities have been linked to the aberrant development and loss of neural progenitor cells (NPCs) (Cugola et al, 2016;Gabriel et al, 2017;Garcez et al, 2016;Li et al, 2016aLi et al, , 2016bTang et al, 2016). The contemporary strain of ZIKV has enhanced replication capacity and a specialized tropism for NPCs (Cugola et al, 2016;Dang et al, 2016;Garcez et al, 2016;Li et al, 2016b;Tang et al, 2016), although other types of cells are susceptible (Tabata et al, 2016;Weisblum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%